Inhibiting SARS‐CoV‐2 infection with lysosomal alkalizers - Gorshkov, Kirill (FASEB J, 2021)
Understanding the SARS‐CoV‐2 virus’ routes of infection, virus–host–protein interactions, and mechanisms of virus‐induced cytopathic effects will greatly aid in the discovery and design of new therapeutics to treat COVID‐19. Chloroquine and hydroxychloroquine, extensively explored as clinical agents for COVID‐19, have multiple cellular effects including alkalizing lysosomes and blocking autophagy as well as exhibiting dose‐limiting toxicities in patients. To identify an alternative lysosome‐based drug repurposing opportunity we evaluated additional lysosomotropic compounds . We found that six of these compounds blocked the cytopathic effect of SARS‐CoV‐2 in Vero E6 cells with half‐maximal effective concentration (EC50) values ranging from 2.0 to 13 μM and selectivity indices (SIs; SI = CC50/EC50) ranging from 1.5‐ to >10‐fold. We demonstrate how the compounds (1) blocked lysosome functioning and autophagy, (2) prevented pseudotyped particle entry, (3) increased lysosomal pH, and (4) that ROC‐325 reduced viral titers in the EpiAirway 3D tissue model. Consistent with these findings, the siRNA knockdown of ATP6V0D1 blocked the HCoV‐NL63 cytopathic effect in LLC‐MK2 cells. Moreover, an analysis of SARS‐CoV‐2 infected Vero E6 cell lysate revealed significant dysregulation of autophagy and lysosomal function, suggesting a contribution of the lysosome to the life cycle of SARS‐CoV‐2. Our findings support targeting the lysosome to combat SARS‐CoV‐2 infections and inhibitors of lysosomal function could become an important component of drug combination therapies aimed at improving treatment and outcomes for COVID‐19.